Flame Luminance Enhancement using Chromaticity Pigmentation for Real Time Fire Detection - Choudhary, Gokul; Pandey, Pankaj (International Journal of Computer Sciences and Engineering, 2025)
Fire detection is a technique through which fire or flame can be detected that alarm in crucial situation. Fire should be detected at real time and required action supposed to be taken immediately. Fire can be detected either by physical sensors or image processing. Some, remote area like forest requires real time detection but physical sensor cannot be placed at well that image processing is more powerful in such areas. Most of the image based recognition technique is processed through flame color detection. Flame color possesses yellow, red and orange that belongs to RGB and CMY color models. Here the proposed system focuses on flame luminance enhancement that increases the color intensity of flame through which fire can be detected with high level of accuracy. Proposed system uses HSL and CMY color models along with chromaticity pigmentation technique that allows to increase particular color intensity for higher true acceptance rate that reduces true rejection rate